Transplacental Transmission of Porcine Epidemic Diarrhea Virus - Ryu, Jihoon; Kang, Gi-Jong; Kim, Onnuri; Park, Jae-Yeon; Shin, Hyun-Jin (Frontiers in Veterinary Science, 2022)
Since the porcine epidemic diarrhea virus (PEDV) is a critical pathogen resulting rapid spreading and high mortality rates in piglets, understanding of the transmission route of PEDV is required for its controlling. Until now, it is well known that PEDV transmission routes are various, such as fecal-oral route, contaminated feed, farmworkers, and transport vehicles, so far. However, unlike several swine-infected viruses, there were no reports of vertical transmission with PEDV. In our study, we confirmed possible vertical transmission of PEDV. We confirmed PEDV in piglet testicles and umbilical cords from PEDV-positive sow. These findings are direct evidence that PEDV is transmitted vertically through placenta. This is the first report on transplacental transmission of PEDV and will be very important information for controlling PED.